JURIDICAL IMPLICATIONS OF THE REVISION OF ARTICLE 47 OF THE TNI LAW ON CIVILIAN SUPREMACY IN INDONESIA - Fredrik Dian Panarawa; Karlinae D. Bangas; Ivans Januardy; Yacob F. Martono (RADJA PUBLIKA, 2026)
The revision of Article 47 of Law Number 3 of 2025 concerning Amendments to Law Number 34 of 2004 on the Indonesian National Armed Forces (Tentara Nasional Indonesia/TNI) has generated debate within Indonesia’s constitutional system, particularly regarding the appointment of active TNI personnel to civilian positions. The expansion of such assignments raises questions concerning its consistency with the principles of civilian supremacy, military professionalism, and the merit system under Law Number 20 of 2023 on the State Civil Apparatus. This study aims to analyze the juridical implications of the revision of Article 47 from the perspective of constitutional law and to examine its conformity with the constitutional principles of the rule of law and post-1998 security sector reform. This study employs normative legal research using statutory, conceptual, and historical approaches through an analysis of primary and secondary legal materials. The findings indicate that, formally, the revision is valid as a legislative product; however, materially, it gives rise to potential normative tensions with the principles of civilian supremacy and the merit-based bureaucratic system. Therefore, more comprehensive implementing regulations and harmonization with civil service regulations are necessary to ensure that the appointment of active military personnel to civilian positions remains within the framework of the rule of law and constitutional democracy.